Comparative Analysis of Image Steganography using SLT, DCT and SLT-DCT Algorithm - Lilik Widyawati; Imam Riadi; Yudi Prayudi (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2020)
Steganography is an interesting science to be studied and researched at this time, because steganography is the science of hiding messages on other digital media so that other parties are not aware of the existence of information in the digital media. Steganography is very effective in maintaining information security, because the existence of this information is obscured so that it is difficult to know where it is. This paper discusses hiding text into images using the Slantlet Transform (SLT) method, Descreate Cosine Transform (DCT) and Hybrid of SLT and DCT. The three methods are implemented in the frequency domain where steganographic imagery is transformed from the spatial domain to the frequency domain and the message bit is inserted into the cover image frequency component. The comparison parameters of these three techniques are based on MSE, PSNR, Capacity & Robustness. From the results of the tests that have been done, it is obtained that the highest PSNR value is generated using the SLT-DCT method, the largest storage capacity is the SLT method while the resistance, SLT-DCT method and DCT method are more resistant to attack than the SLT method.